AB1213-HPR Nurse Sensitive Outcomes in Patients with Rheumatoid Arthritis (RA) – a Systematic Literature Review. (9th June 2015) - Kelly, A.; McKee, G.; van Eijk-Hustings, Y.; Ndosi, M.; O'Sullivan, D.; Menzies, V.; Carter, S.; Richards, P.; Minnock, P.
Abstract : Background: Rheumatology nursing is a practice specialty and contributes significantly to the management of patients with rheumatic musculoskeletal diseases (1, 2). Rheumatology nursing role development follows a worldwide tendency among healthcare practitioners to provide a more proactive, evidence-based and patient-preference-based care. EULAR recommendations have highlighted the need for further research about the contribution of rheumatology nursing to patient outcome in order to strengthen research results. A core set of relevant patient outcomes should be defined and nursing domains, roles and interventions should be clarified (3). Objectives: To identify patient outcomes and measures which were sensitive to nurse interventions in patients with RA. Methods: A systematic literature review (SLR) was conducted using standard recognised databases: PUBMED, CINAHL, Ovid Nursing, PSYCHinfo, The COCHRANE Library. Inclusion criteria were: RA, Age >18years, Nurse. Relevant papers were selected independently by pairs of international reviewers including patient research partners and reviewed using Critical Appraisal Skills Programme (CASP) criteria. Results: Of the 749 papers identified, 8 were included in this review: 5 randomised controlled trials and 3 longitudinal observational studies. Identified rheumatology nursing interventions included: clinical assessment of disease activity, pain and symptom management, patient education on disease process and medication management, drug safety monitoring, medication changes and consultation/referrals to other health professionals. Outcome measures identified included: Arthritis Impact Measurement Scale, Health Assessment Questionnaire, Leeds Satisfaction Questionnaire, fatigue, early morning stiffness duration, six American College of Rheumatology core outcome measures (excluding radiographic progression), the composite Disease Activity Score, RAND-36 health survey, McMaster Toronto Arthritis Patient Preference Disability Questionnaire (MACTAR), RA Quality of Life Questionnaire, SF-36, Patient Knowledge Questionnaire. Also recorded were grip strength, walk test, changes in drug therapy and number of consultation with/referrals to health professions Conclusions: The SLR identified relevant interventions and outcomes. To identify a core set of nurse sensitive outcomes in RA further exploration of patients' and health professionals' opinions are needed. References: Carr A, Defining the Extended Clinical Role for Allied Health Professionals in Rheumatology. ARC Conference Proceedings No. 12. Chesterfield, Arthritis Research Campaign, 2001. ANA/RNS, Rheumatology Nursing: Scope and Standards of Practice, A.a.t.R.N. Society, Editor. 2013: Siver Spring MD. Van Eijk-Hustings, Y, et al., EULAR recommendations for the role of the nurse in the management of chronic inflammatory arthritis. Ann Rheum Dis, 2012. 71(1): p.13-9. Disclosure of Interest: None declared